Tóth Lajos akadémikus, a polgári jog professzora, a Debreceni m. kir. Tisza István-Tudományegyetem 1934/35. évi Rector Magnificusa - Balogh, Judit (Gerundium, 2019)
Lajos Tóth, Professor of Civil Law, the Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen during the academic year 1933/1934. Prof. Dr. Lajos Tóth (1876–1936), Member of the Hungarian Academy of Sciences, was a professor strongly bound to Debrecen. He was born in Debrecen, he completed his schools there too, and (after studying law in Budapest) he worked at he Faculty of Law from its opening in 1914 until the end of his life. The study gives a summary of his life and professional results as a professor of civil law, but focuses on his role in the administration of the university. His most active period of leadership was the academic year of 1919–20, when in fact he was the leader of the university as vice rector because of the illness of Rector Gyula Kenézy. In addition, he succeeded in completing the justification procedures during the revolutions. Although, he was ill, he was trying to solve his activities as the rector of the university in the academic year of 1934–35. Beside his academic work, he took part in the social politics of Debrecen, too. He was a member of the municipal committee of the city; he was office-holder of the Transtibiscan Reformed Church District for decades. From 1930, he was Senator in the upper house of the Hungarian Parliament, as a representative of the University of Debrecen.